Inflationary price trends in India since 1939 - Singh, D Bright (London : Asia Pub. House, 1961)
This book attempts to analyse the general pattern of price trends in India since 1939 and examines how far such factor as war finance, developmental outlays, balance of payments position and production trends in the country influenced prices. It also looks at how the rapid rise in prices affected the consumption habits and standards of life of the people.
Includes bibliographical footnotes and index
asm 22/01/2019
Loans
Keywords: Prices; Inflation (Finance); Economic history; India